The Role of Meatballs as a Means of Culinary Diplomacy in Building Indonesia’s International Image: Peran Bakso sebagai Sarana Diplomasi Kuliner dalam Membangun Citra Internasional Indonesia - -, Anggiana Chantika Fitri; -, Made Panji Teguh Santoso (Kajian Hubungan Internasional, 2025)
This study discusses meatballs as a culinary icon used in Indonesia's participatory gastrodiplomacy strategy to build cultural image and strengthen international relations. The problem raised is the absence of a systematic study that elaborates on the role of meatballs in public diplomacy practices, both by state and non-state actors. This study uses a qualitative approach with a case study design based on a literature review and the constructivism paradigm. Data were obtained from nine literature documents, both academic and institutional, which were analyzed using thematic content analysis methods. The results of the study indicate that meatballs are able to become an effective medium for cultural communication in various diplomatic contexts: from official activities of the Indonesian Embassy, ​​informal diplomacy by diaspora communities and students, to city diplomacy through inter-regional cooperation. These findings indicate that the meaning and function of meatballs in diplomacy are flexible, negotiable, and have great potential to form positive perceptions of Indonesia. The conclusion of this study emphasizes the importance of strengthening gastrodiplomacy strategies based on culinary icons that are integrated with the active role of various stakeholders, including diaspora and local actors, to support Indonesia's cultural diplomacy sustainably. Keywords: (meatballs, gastrodiplomacy, cultural diplomacy, national branding, constructivism)